PRODUCT DATA MANAGEMENT FOR FINNISH SMALL AND MEDIUM-SIZED MANUFACTURING ENTERPRISES - Towards a viable information system concept - Suutari, Jari (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Product Data Management (PDM) systems have been utilized within companies since the 1980s. Mainly the PDM systems have been used by large companies. This thesis presents the premise that small and medium-sized companies can also benefit from utilizing the Product Data Management systems. Furthermore, the starting point for the thesis is that the existing PDM systems are either too expensive or do not properly respond to the requirements SMEs have. The aim of this study is to investigate what kinds of requirements and special features SMEs, operating in Finnish manufacturing industry, have towards Product Data Management. Additionally, the target is to create a conceptual model that could fulfill the specified requirements. The research has been carried out as a qualitative case study, in which the research data was collected from ten Finnish companies operating in manufacturing industry. The research data is formed by interviewing key personnel from the case companies. After this, the data formed from the interviews has been processed to comprise a generic set of information system requirements and the information system concept supporting it. The commercialization of the concept is studied in the thesis from the perspective of system development. The aim was to create a conceptual model, which would be economically feasible for both, a company utilizing the system and for a company developing it. For this reason, the thesis has sought ways to scale the system development effort for multiple simultaneous cases. The main methods found were to utilize platform-based thinking and a way to generalize the system requirements, or in other words abstracting the requirements of an information system. The results of the research highlight the special features Finnish manufacturing SMEs have towards PDM. The most significant of the special features is the usage of project model to manage the order-to-delivery –process. This differs significantly from the traditional concepts of Product Data Management presented in the literature. Furthermore, as a research result, this thesis presents a conceptual model of a PDM system, which would be viable for the case companies interviewed during the research. As a by-product, this research presents a synthesized model, found from the literature, to abstract information system requirements. In addition to this, the strategic importance and categorization of information systems within companies has been discussed from the perspective of information system customizations.

Tuotetiedonhallintajärjestelmät ovat olleet yrityksissä käytössä jo 1980-luvulta saakka. Pääasiassa kyseisiä tietojärjestelmiä ovat käyttäneet suuret yritykset. Tämä tutkielma lähtee olettamuksesta, että myös pienet ja keskisuuret yritykset pystyvät hyötymään toiminnassaan tuotetiedonhallintajärjestelmistä. Lisäksi oletuksena on, että nykyiset tuotetiedonhallintajärjestelmät ovat joko liian kalliita tai niiden toiminnollisuus ei vastaa kunnolla Pk-yritysten tarpeita. Tämän tutkielman tavoitteena on selvittää minkälaisia vaatimuksia ja erityispiirteitä suomalaisilla valmistavan teollisuuden Pk-yrityksillä on, sekä mallintaa konseptitasolla näihin vaatimuksiin sopiva tuotetietohallinnan tietojärjestelmä. Tutkimus on suoritettu kvalitatiivisena tapaustutkimuksena, jonka tutkimusaineisto on kerätty kymmeneltä suomalaiselta valmistavan teollisuuden yritykseltä. Tutkimusaineisto on muodostettu haastattelemalla kohdeyritysten avainhenkilöitä. Haastatteluista muodostunutta aineistoa on tämän jälkeen jalostettu, josta on muodostunut yleiset tietojärjestelmävaatimukset, sekä niitä tukeva tietojärjestelmäkonsepti. Tietojärjestelmäkonseptin kaupallistamista on tutkielmassa pohdittu myös järjestelmäkehityksen näkökulmasta. Tavoitteena oli mallintaa tietojärjestelmäkonsepti, joka olisi taloudellisesti järkevä sekä järjestelmää kehittävän, että järjestelmää hyödyntävän yrityksen kannalta. Edellä mainitusta syystä, tutkielmassa on etsitty keinoja järjestelmäkehityksen skaalaamiseksi soveltuvaksi monelle yhtäaikaiselle kohdeyritykselle. Päällimmäiseksi keinoksi muodostuivat alustapohjainen lähestyminen ja menetelmät tietojärjestelmävaatimusten yleistämiseen, tai toisin sanoen abstrahointiin. Tutkimuksen loppupäätelmänä tuodaan esiin suomalaisten yritysten erityispiirteitä, jotka vaikuttavat tuotetiedonhallintajärjestelmien toiminnollisiin vaatimuksiin. Merkittävimpänä erityispiirteenä nostetaan asiakastoimituksien hoitaminen projektimallilla, mikä poikkeaa huomattavasti kirjallisuuden käsityksestä perinteisistä tuotetiedonhallinnan konsepteista. Työn lopussa esitetään alustapohjainen tietojärjestelmäkonsepti, joka olisi toteuttamiskelpoinen ja soveltuva tutkimuksen otantaryhmälle. Tämän tutkimustyön oheistuotteena syntyi myös synteesimalli kirjallisuudessa esitetyistä tavoista abstrahoida tietojärjestelmävaatimuksia. Lisäksi tietojärjestelmien strategista merkitystä ja kategorisointia yrityksissä on pohdittu järjestelmäkustomointien näkökulmasta.